Multiple tumors: Association of digestive neoplasms and lymphomas - Viola Alles, Alberto; Glausiuss, José; Vázquez, Tabaré; Priario, Julio C.; Kasdorf, Helmuth (Cirugía del Uruguay, 1979)
The authors report three cases of tumoraT lymphopathies: one Hodgkin's disease and 2 non - Hodgkins lymphomas. During evolution a seco·nd tumor of epithelial origin appeared in digesti ve tract. 2 of these patients died as a consequence of the second neoplasia respectively at 2 and 4 months; the other survived for 12 months. The paper discusses oncogenic mechanisms of multiple tumors, weighing modifications to cell immunity in advanced stages of lymphomas and the possible role of radiations and/or cystostatic therapy and their sequence in different protocols.